An Introductory Note from the General Editor, with Recourse to Plato and Eukleidas - Molinari, Dr Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2019)
When Plato wrote the final prayer in the Phaedrus quoted on the previous page, he had recently returned from a tumultuous stay in Sicily. He went there to convince Dionysius I (the Elder) to reject his lifestyle of debauchery and turn to the philosophical life, essentially to become the first philosopher king. Dionysius did not heed Plato’s advice, and neither did his son, Dionysius the Younger. In fact, there were times during Plato’s several trips to the island that the philosopher was risking his own life to promote his idea of the just society. Plato’s name was slandered, and members of the court tried to convince Dionysius that Plato was there to help overthrow the tyrant. At one point, Plato actually had to leave Syracuse and lodge with mercenaries, some of the most ruthless characters known in antiquity. Despite the mishaps, Plato’s stay was not all bad, and evidently quite inspiring: For those of you unfamiliar with the Phaedrus, it is a dialogue that concerns Beauty in relation to the soul, and the role of love and wonder in the process of self-appropriation and acquisition of knowledge of ultimate reality, which for Plato go hand-in-hand. Throughout its pages, we are told a story of how Beauty is the only transcendental form we can glimpse here on earth, and it is through beatific vision that we are led, following Zeus and a procession of gods, to an even greater vision of the ‘colorless, formless, and truly intangible οὐσια ὄντως οὖσα.’ (247c) I find it interesting that, if we look at the numismatic context of Sicily when Plato visited, in the first quarter of the fourth century BC, we find that he was exposed to arguably the greatest numismatic masterpieces ever struck, ancient or modern. Is it any surprise, after viewing the work of artists like Kimon, Eukleidas, and Eumenes, featuring spectacular levels of craftsmanship, that Plato composed a dialogue concerning the very nature of Beauty in its relation to what he saw as the fundamental principle of human existence?